MANUNGGALING KAWULA GUSTI DALAM PRESPEKTIF TAUHID ISLAM: KAJIAN KRITIS TERHADAP SPIRITUALITAS KEJAWEN - Anwar, Choirul; Nurrohim, Ahmad (Penerbit Lafadz Jaya, 2026)
The spiritual doctrine of Manunggaling Kawula Gusti in Javanese Kejawen mysticism emphasizes inner union between servant (kawula) and God (Gusti) yet raises theological concerns from Islamic tauhid perspective regarding essential unity. This study critically examines the doctrine's origins, concepts, and compatibility with Islamic monotheism. Employing a qualitative literature study method with descriptive analysis, the population comprises primary Kejawen texts (e.g., Zoetmulder, Simuh) and Islamic theological sources (e.g., Ibn Taimiyyah, Al-Ghazali); purposive sampling targets thematic relevance. Instruments include textual documents, analyzed via content and comparative analysis with source triangulation. Findings reveal conceptual overlaps in spiritual purification and fanāʾ (ego annihilation) but fundamental divergence: Kejawen implies potential ontological merger, rejected by tauhid upholding Creator-creation distinction. Conclusion advocates symbolic reinterpretation within Sunni Sufism for cultural accommodation without doctrinal deviation.